ESTIMATE OF EFFICIENCY OF MULTIPLE RETICULAR IMPLANTS APPLICATION IN THE SEVERE ABDOMINAL WALL MALFORMATIONS’ INTRAPERITONEAL ALLOPLASTY - Feleshtynskyy, J.P.; Lysenko, R.B.; Mishchuk, V.V. (World of Medicine and Biology, 2015)
A optimale experymental intraperytoneal alloplasty (IPOM) of anterior abdominal wall (AAW) in abdominal wall complex defects (AWCD). Perform experymental study at 80 rats with definition tissue reaction AAW and the inner organs in intraperytoneal typical deployment different meshes implantats. Proved, something intraperytoneal deployment of composite mesh implants antyadhezyv with no pavement development adgesions with inner organs and optimal integration with a tissues of AAW and small deformation, promotes formation of neoperytoneum. This confirms the rest of this significant effectieveness alloplasty AAW at surgical treatment of AWCD.
Keywords: aloplastyka; anterior abdominal wall; mesh implants